Aplikasi Absensi Karyawan Berbasis Android Dengan Penerapan QR Code Disertai Foto Diri Dan Lokasi Sebagai Validasi Studi Kasus: PT.Selindo Alpha - Muhammad Himyar; Muhamad Femy Mulya; Johny Hizkia Siringo Ringo (Teknik Informatika, 2021)
One of the main components in the world of work is attendance or attendance lists. With this attendance, work in a company can run in a structured and organized manner. Along with high mobility, the use of smartphones is now also used to support work activities, one of which is to do attendance. However, not many companies have used this technology in their companies. This research aims to build an automated employee attendance system based on android by using a QR code accompanied by a photo of yourself and an online LBS (Location Based System). In this application, it allows users to fill in attendance easily and can be used at any time, so that employees who have limited time and do not have time to fill out the attendance list form can easily fill out the attendance list. This application was developed by applying the agile scrum model and designed using UML and Java-based programming language and for the testing process using black box testing. The research was conducted by collecting data through literature study. This research produces applications that have been tested in terms of usability and are declared valid or according to user needs